6(3x+5)=5(x-4)+18

Simple and best practice solution for 6(3x+5)=5(x-4)+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3x+5)=5(x-4)+18 equation:


Simplifying
6(3x + 5) = 5(x + -4) + 18

Reorder the terms:
6(5 + 3x) = 5(x + -4) + 18
(5 * 6 + 3x * 6) = 5(x + -4) + 18
(30 + 18x) = 5(x + -4) + 18

Reorder the terms:
30 + 18x = 5(-4 + x) + 18
30 + 18x = (-4 * 5 + x * 5) + 18
30 + 18x = (-20 + 5x) + 18

Reorder the terms:
30 + 18x = -20 + 18 + 5x

Combine like terms: -20 + 18 = -2
30 + 18x = -2 + 5x

Solving
30 + 18x = -2 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
30 + 18x + -5x = -2 + 5x + -5x

Combine like terms: 18x + -5x = 13x
30 + 13x = -2 + 5x + -5x

Combine like terms: 5x + -5x = 0
30 + 13x = -2 + 0
30 + 13x = -2

Add '-30' to each side of the equation.
30 + -30 + 13x = -2 + -30

Combine like terms: 30 + -30 = 0
0 + 13x = -2 + -30
13x = -2 + -30

Combine like terms: -2 + -30 = -32
13x = -32

Divide each side by '13'.
x = -2.461538462

Simplifying
x = -2.461538462

See similar equations:

| 4+2(-9z+4)=4(-z-1)-1 | | -3.6u+1.8=-1.8 | | -0.7-5.6=-3.5 | | 25*100=5*(500-x) | | 27a^2+39ad+14d^2= | | 12d^2-13ds-35s^2= | | 20b^3-41b^2+20b= | | 5a-2=a+18 | | 7x+38=248 | | dx+b=2(x-d) | | 44b^2-208b-60= | | 9m+3m= | | 9k=3 | | 32r^5-60r^4-27r^3= | | 3x^3+x^2-8x+4=0 | | 7000d=63.5 | | 0.4v+2.4=-5.4v-3.4 | | 0.4a+2.4=-5.4v-3.4 | | 32s^5-76s^4-33s^3= | | -3+(5z+9)=(7z+5)-6 | | 12x^2-8xy-20y^2= | | -0.8z+3.3=0.9 | | -6-6+20x=5(4x-5)+13 | | -0.8a+3.3=9.9 | | -3x-10=-4 | | 3a=9a+24 | | 6g^2+13gc+6c^2= | | -2t-1=3t-16 | | 3z-13=-10 | | 4x-2y=-12 | | -2+6=4v-6v | | 42m^2-29mn-5n^2= |

Equations solver categories